Replacement of fish protein in fish feed : effects on the yeast flora in the gut of Arctic charr (Salvelinus alpinus) - Rydmark, Hanna (SLU/Dept. of Animal Nutrition and Management (until 231231), 2023)
The aim with this study was to investigate how feeds with different protein sources influence the levels and composition of the yeast flora in the gut of Arctic charr (Salvelinus alpinus). Arctic charr were fed for two weeks on a control diet (C) with fishmeal (FM) or experimental diets with 40% FM replaced by yeast (Saccharomyces cerevisiae) (Y), meal from blue mussel (Mytilus edulis) (M) or a feed with Baltic Sea originated protein; 33% FM, 33% mussel meal (MM) and 33% S. cerevisiae referred to as Baltic blend (BB). The effect of the different feeds was evaluated based on fish growth and the effects on the microbial population, with a focus on yeasts, in different parts of the gut (stomach (S), pylorus (P), mid intestine (MI) and distal intestine (DI)). Differences in the development of the yeast flora composition and yeast loads were investigated using agar plate counts and yeast species identification using polymerase chain reaction (PCR) amplification combined with sequencing of the 28S rRNA gene. The amount of bacteria and moulds were also estimated when examining the agar plates. In addition, the different feeds were analysed for yeast load, yeast species composition and diversity. The study showed that there were differences in yeast load in the gut linked to diet, where the diet containing S. cerevisiae (Y) had a higher yeast load compared to the other diets both before (C: p = 0.003, M: p = 0.016, BB: p = 0.0007) and after the diet intervention (C: p = 0.024, M: p = 0.001, BB: p = 0.001). Differences in amount of yeast could also be linked to time (i.e., before and after) (p = 0.0009) with greater yeast loads at the end of the experiment, where the yeast load in the gut ranged between 4.1–7.5 log CFU g-1 after two weeks of dietary treatment. However, no differences between gut segments were found on yeast load or yeast composition. The domination yeast species found in gut in all diets were Debaryomyces hansenii (68–70% of yeast isolates) followed by Debaryomyces sp. (19–24%). Both D. hansenii and ...